Analisis Geografi Terhadap Tingginya Pernikahan Usia Muda Di Kecamatan Blora Kabupaten Blora Tahun 2011 Dan 2015 - Nur Rahmi, Isna; , Dra. Umrotun, M.Si (2017)
Marriage is an important and sacred event that is done by a couple of man and woman with purpose to create household. Young marriage nowadays often occurs either in the town or village, one of it is in Blora Sub-District, Blora District which is be affected by several factors, that are education, economic, environment, and culture. This research is undertaken in Blora Sub-District, Blora District Year 2011 and 2015 with comparing two villages, Andongrejo and Temurejo, and Karangjati village. This research aims to: (1) Study about young marriage in Blora District, Blora Regency, with ratio between village and town in 2011 and 2015, (2) Know the factors that are affecting the occurs of young marriage. This research method is survey, for sampling use "simple random sampling" so that the population has the same proportion, samples have been determined in AndongrejoDistrict and Karangjati village in 2011, TemurejoDistrict and Karangjati village in 2015. The result shows declining of young marriage in 2015 rather than 2011 with high proportion of young marriage, most of this occurred in town or village which included in scope of town, most of females choose young marriage with last education of senior high school in village or town, most of enterprise job is done by people who married in young age, population incomes approximately Rp. 500.000,00 - Rp. 1.000.000,00, education can hinder young marriage, young age marriage in town region is higher because of environment, while in village tends to economic and environment factors.